Hubungan Pengetahaun, Pola Makan dan Dukungan Keluarga Dengan Kejadian Hipertensi Pada Lansia - Lilipory, Mevi; Talakua, Geresya (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2022)
Hypertension is a non-communicable disease, often known as high blood pressure with the condition of blood vessels experiencing a systemic increase or in the long term above normal 140/90 mmHg. Lack of knowledge, lack of family support and the wrong diet can increase the risk of increasing hypertension in a person. This study aims to determine the relationship between knowledge, diet and family support with the incidence of hypertension in the elderly in Porto. The research design used was an analytical descriptive survey with a cross sectional approach. With the results of research conducted the number of samples in this study were 53 respondents studied. The results were tested using the chi-square test, it was found that there was a relationship between knowledge and the incidence of hypertension in the elderly with a p value = 0.000, there was a relationship between diet and the incidence of hypertension in the elderly with a p value = 0.002, and there was a relationship between family support and the incidence of hypertension in the elderly. elderly with p = 0.000. From this research, it is suggested to the elderly and their families in order to increase their knowledge related to hypertension and regulate a good diet and add support to the elderly.Keywords: Elderly, Knowledge, Diet, Family Support, Hypertension Incidence